Visual Identity “Licincyin” As A Promotional Strategy For Processed Eel Home Industrial Products - Qurrotul A.FS, Nurul Izza; Yunianto, Ipung Kurniawan (UNIVERSITAS PAKUAN, 2019)
Society must begin to adapt to the new way of life, often referred to as the 'new normal life.' This transitional period has led to significant changes in societal behavior. One of these changes is the shift in food consumption patterns. With the increased demand, the market segment predictions and the scope of frozen food producers are expected to expand further.Frozen smoked eel processing products in Indonesia are not the only ones, but there are still very few business actors. This is a great opportunity for the